"Pennadas Furtivas": política, humor e crítica na imprensa de Uberaba/MG (1899-1903) - Oliveira, Raniele Duarte (2021)
The objective of the work is to analyze a newspaper column entitled “Pennadas Furtivas”. Published in the uberabense journal Lavoura e Comércio, this column, between the years 1899 and 1903, was the space for the writing of Manoel Felipe de Souza. By encouraging progress, modernity and civilization, this columnist produced chronicles for the sheet. From the perspective that newspapers are both a source and objects of research, to understand the meaning of the column, mappings were made that took into account the press in the city and the content of the journal's columns, in particular of the “Pennadas Furtivas”. Both its author and the chronicles themselves carry a complexity, because one thing is how Manoel Felipe de Souza saw himself and put himself in the newspaper, another is what it actually was. The fierce way in which he treated the issues of the city in his chronicles it was often a reflection of a resentful tone, of someone who talked to the economic elites, wrote to them, amused them and made them laugh, but was not part of them. While the most serious debates took place on the pages of the periodical involving the political issue of the state of Minas Gerais, Manoel Felipe de Souza, born of the Belle Époque , took on several roles to ensure his survival. He was a multifaceted man, interior intellectual, that with differences in performance used his pen as a weapon, because creatively and provocatively appropriated the civilizational discourse to boost the overcoming of practices seen as backward.